Modelling of dielectric barrier discharge plasma actuators for direct numerical simulations - Brauner,T; Laizet,S; Benard,N; Moreau,E (AAAI, 2016)
In recent years the development of devices known as plasma actuators has advancedthe promise of controlling flows in new ways that increase lift, reduce drag and improveaerodynamic efficiencies; advances that may lead to safer, more efficient and quieter aircraft.The large number of parameters (location of the actuator, orientation, size, relativeplacement of the embedded and exposed electrodes, materials, applied voltage, frequency)affecting the performance of plasma actuators makes their development, testing and optimisationa very complicated task. Several approaches have been proposed for developingnumerical models for plasma actuators. The discharge can be modelled by physics-basedkinetic methods based on first principles, by semi-empirical phenomenological approachesand by PIV-based methods where the discharge is replaced by a steady-state body force.The latter approach receives a recent interest for its easy implementation in RANS andU-RANS solvers. Here, a forcing term extracted from experiments is implemented intoour high-order Navier-Stokes solver (DNS) in order to evaluate its robustness and abilityto mimic the effects of a surface dielectric barrier discharge. This experimental forcingterm is compared to the numerical forcing term developed by Suzen & Huang (1, 2) withan emphasis on the importance of the wall-normal component of each model.